Customer journeys: a systematic literature review. Issue 2 (8th February 2018) - Følstad, Asbjørn; Kvale, Knut
Abstract : Purpose: Customer journeys have become an increasingly important topic in service management and design. The purpose of this paper is to review customer journey terminology and approaches within the research literature prior to 2013, mainly from the fields of design, management, and marketing. Design/methodology/approach: The study was conducted as a systematic literature review. Searches in Google Scholar, Scopus, Web of Knowledge, ACM Digital Library, and ScienceDirect identified 45 papers for the analysis. The papers were analyzed with respect to customer journey terminology and approaches, the relation to customer experience, the referenced background, and the use of visualizations. Findings: Across the reviewed literature, customer journeys are described not only as a means to take the viewpoint of the customer, but also to reach insight into their experiences. A rich and at times incoherent customer journey terminology is analyzed and discussed, as are two emerging customer journey approaches: customer journey mapping (analysis of a service process "as is") and customer journey proposition (generative activities leading toward a possible service "to be"). Research limitations/implications: The review is limited to analyzing and making claims on research papers that explicitly apply the term customer journey. In most of the reviewed papers, customer journeys are not the main object of interest but are discussed as one of several topics. Practical implications: A nuanced discussion of customer journey terminology and approaches is provided, supporting the practical application of a customer journey perspective. Originality/value: The review contributes a needed common basis for future customer journey research and practice.